EFFECTIVENESS OF LOW-COST CUSTOMIZED SADDLE PILLOW ON PAIN IN POST-EPISIOTOMY PATIENTS - Krishnan, Nair Shalini; M, Anbupriya; Vpr, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To examine the effectiveness of customized saddle pillow for pain in post-episiotomy patients and also to analyze the duration of sitting for breastfeeding and other functional activities following episiotomy. Methods: A total of 28 postnatal mothers who have undergone episiotomy were included in the study based on the inclusion criteria and were divided conveniently into an experimental group (n=16) and control group (n=12). Both the groups received the conventional physiotherapy protocol, but experimental group patients, in addition, were provided with customized saddle pillow. Customized saddle pillow was used by the patients from postnatal day (PND) 0 to PND 2. Pre- and post-test values for pain were assessed through the numerical pain rating scale (NPRS). In addition, data such as duration of sitting for breastfeeding and other functional activities were collected through sitting tracker. Results: The study manifested the effectiveness of low-cost customized saddle pillow in reducing perineal pain (p=0.01) and increase in sitting duration (p=0.01) in post-episiotomy patients compared to the control group. Conclusion: Among the postnatal mothers selected for the study the mothers who used customized saddle pillow experienced a reduction in pain as well as the better sitting duration for breastfeeding. The research recommends mothers who underwent episiotomy to use the low-cost saddle pillows for healthier breastfeeding and pain-free life.